PERANCANGAN DAN IMPLEMENTASI SISTEM E-COMMERCE PADA UMKM BATIK DI KABUPATEN JOMBANG - Renny Sari Sisfor; Oki Anita Candra Dewi; Rizky Noviasri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
The rapid development of information technology (IT) is directly proportional to the increase of the middle-class economy segment. As one of the original products of the Indonesian people, batik and all its variety is not spared from the impact of IT development. To introduce one of the various types of batik craft typical of Jombang Regency, the author partnered with UD Litabena and UD Batik Colet as micro, small-medium enterprise (SME) to participate in introducing the region's distinctive batik craft. Therefore, the implementation of the community partnership program aims to design and implement e-supply chain in the form of e-commerce which is useful to facilitate SME to sell Jombang’s batik craft products in all circles in Indonesia. There are 5 stages in the implementation of this program, including surveying the business process of making Jombang batik craft, determining the superior motives of MSMEs, designing system requirements, developing systems, and implementing web-based e-commerce systems. The conclusion obtained is, the system was designed by Enterprise Architect software, and the web-based e-commerce was built with the WooCommerce plugin.